KORELASI MODEL GROUP INVESTIGATION DENGAN KEMAMPUAN BERPIKIR KREATIF DAN KEMAMPUAN PEMECAHAN MASALAH - Umar Soleh; Ferry Ferdianto; Setiyani Setiyani (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
The purpose of this research is to know the relationship of Group Investigation model with creative thinking ability and problem solving ability. Model Group Investigation is a group-based learning model where students are given opportunities to discuss, think critically, and be responsible for the learning. The research method used is experimental method, with sampling technique used is Purposive Sample. The instrument used in this research is the observation sheet of student activity, the question of creative thinking ability and the problem solving test problem. The test used is Pearson Product Moment correlation test, ANOVA Factorial test, and uji t. The results of this study are: (1) student activity in learning mathematics by using Group Investigation model overall percentage reaches 65,6% and included in good category; (2) there is correlation of Group Investigation model with creative thinking ability; (3) there is correlation of Group Investigation model with problem solving ability; (4) there is a correlation of Group Investigation model with creative thinking ability and problem-solving ability; (5) there is difference of average ability of creative thinking and problem solving ability between experiment class student and control class student, with mean value of experiment class is 76,60 whereas mean value of control class is 68,57.